PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS MULTILITERASI DALAM PENDIDIKAN AGAMA ISLAM - Siti Roudhotul Jannah; Muhammad Riyadh; Wahyu Eko Purwanto; Nur Rahman Utsman; Muhammad Nurudin (JIP: Jurnal Ilmu Pendidikan, 2025)
This study aims to develop interactive multiliteracy-based learning media in Islamic Religious Education (IRE) that is suitable for the characteristics of 21st century students. The background of this study is the need for an adaptive learning approach to technological developments, as well as the ability to engage in multiple literacies, including digital, visual, media, and critical literacy. This study uses the Research and Development (R&D) model by Borg & Gall, which consists of ten stages, modified into seven stages for efficiency. The test subjects consisted of fifth-grade elementary school students and IRE teachers. The developed media is an interactive web-based application that combines narrative text, videos, animations, digital quizzes, and a simple discussion forum. Validation by subject matter and media experts indicated that the product is highly feasible with an average score of 90.5%. Limited testing showed a significant increase in students' interest in learning and active engagement in the learning process. In addition, students demonstrated better ability in understanding PAI material through the multiliteracy approach provided in the media. Teachers' responses to the use of the media were also positive, particularly in terms of flexibility, visual appeal, and the effectiveness of conveying Islamic values. The implications of this study indicate that the integration of multiliteracy in interactive learning media can address the challenges of PAI learning in the digital era. The development of similar media is recommended for wider application, with content adaptation according to educational levels and student characteristics. This study contributes to the development of technology-based learning innovations that support the formation of students' religious character through contextual, communicative, and transformative approaches.